2002
DOI: 10.1023/a:1020958517788
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The spatial arrangement of some genetic elements relative to chromosome territories and in parallel with the cell nucleus was investigated in human lymphocytes. The structure of the chromosome territories was studied in chromosomes containing regions (clusters) of highly expressed genes (HSA 9, 17) and those without such clusters (HSA 8, 13). In chromosomes containing highly expressed regions, the elements pertaining to these regions were found close to the centre of the nucleus on the inner sides of chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…However, our hybrid model provides strong evidence that the chromatin architecture around a DSB may affect the probability of translocation between particular loci more strongly than the mutual distance between the loci in the nucleus if this distance is not large enough to be dominant [75]. As the functional architecture of chromatin determines both the nuclear gene topology [44][45][46]130,[194][195][196][197] and the vectors (extent and directions) of individual DSB movements relative to each other, it also defines the probability of mutual DSB interaction [48,75].…”
Section: Incorrect Dsb Repair Formation Of Chromosomal Aberrations Amentioning
confidence: 87%
See 1 more Smart Citation
“…However, our hybrid model provides strong evidence that the chromatin architecture around a DSB may affect the probability of translocation between particular loci more strongly than the mutual distance between the loci in the nucleus if this distance is not large enough to be dominant [75]. As the functional architecture of chromatin determines both the nuclear gene topology [44][45][46]130,[194][195][196][197] and the vectors (extent and directions) of individual DSB movements relative to each other, it also defines the probability of mutual DSB interaction [48,75].…”
Section: Incorrect Dsb Repair Formation Of Chromosomal Aberrations Amentioning
confidence: 87%
“…Moreover, chromatin is hierarchically organized at multiple scale levels, which leads to the formation of structurally and functionally distinct chromatin domains [44][45][46][47], with which radiation interacts in a specific way and creates DNA lesions with different requirements for repair (reviewed in [48][49][50][51][52]). The chemical properties of the broken DNA ends were the first local factor ( Figure 1D) recognized to dramatically affect the ability of repair enzymes to rejoin DSBs [53].…”
Section: Global Versus Local Dsb Repair Pathway Selection and Regulationmentioning
confidence: 99%
“…The influence of transcriptional activity on gene positioning in the nucleus has been a controversial issue (for review, see Bartova and Kozubek 2006; Kosak and Groudine 2004; Lanctot et al 2007; Parada et al 2004). Lukasova et al 2002 and Scheuermann et al 2004 suggested an interior nuclear position of transcribed genes, compared to non-transcribed genes in a given cell type. As local gene density was not considered in these studies, these observations may rather reflect gene density than the transcriptional activity of a studied gene per se.…”
Section: Discussionmentioning
confidence: 99%
“…One example of such domains is the distinction between decondensed, transcriptionally active euchromatin and tightly compacted heterochromatin generally to be assumed to be inactive [ 10 , 11 , 12 , 13 , 14 ]. Gene-rich regions tend to be located towards the nuclear interior whereas gene-poor regions are generally found towards the periphery [ 15 , 16 , 17 , 18 ]. Up-regulation of genes during tumour genesis or DNA radiation damage response as well as DNA double strand break repair mechanisms were shown to be associated with re-organisation of chromosome territories [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%